Quality improvement programme reduces errors in oral medication preparation and administration through feeding tubes - Pereira, Rosana Aparecida (BMJ Open Qual, 2020)
BACKGROUND: Patients with nasogastric/nasoenteric tube (NGT/NET) are at increased risk of adverse outcomes due to errors occurring during oral medication preparation and administration. AIM: To implement a quality improvement programme to reduce the proportion of errors in oral medication preparation and administration through NGT/NET in adult patients. METHODS: An observational study was carried out, comparing outcome measures before and after implementation of the integrated quality programme to improve oral medication preparation and administration through NGT/NET. A collaborative approach based on Plan-Do-Study-Act (PDSA) cycle was used and feedback was given during multidisciplinary meetings. INTERVENTIONS: Good practice guidance for oral medication preparation and administration through NGT/NET was developed and implemented at the hospital sites; nurses were given formal training to use the good practice guidance; a printed list of oral medications that should never be crushed was provided to all members of the multidisciplinary team, and a printed table containing therapeutic alternatives for drugs that should never be crushed was provided to prescribers at the prescribing room. RESULTS: Improvement was observed in the following measures: crushing enteric-coated tablets and mixing drugs during medication preparation (from 54.9% in phase I to 26.2% in phase II; p 0.0010) and triturating pharmaceutical form of modified action or dragee (from 32.8 in phase I to 19.7 in phase II; p 0.0010). Worsening was observed though in the following measures: crush compressed to a fine and homogeneous powder (from 7.4%% in phase I to 95% phase II; p 0.0010) and feeding tube obstruction (from 41.8% in phase I to 52.5% phase II; p 0.0950). CONCLUSION: Our results highlight how a collaborative quality improvement approach based on PDSA cycles can meet the challenge of reducing the proportion of errors in oral medication preparation and administration through NGT/NET in adult patients. Some changes may lead to unintended consequences though. Thus, continuous monitoring for these consequences will help caregivers to prevent poor patient outcomes.